Genital Herpes in a STD outpatient clinic in Lisbon - Lopo, Sílvia (2017)
Introduction: Genital Herpes is the major cause of genito-ulcerative disease affecting a considerable number of individuals worldwide and is a chronic, life-long viral infection caused by both HSV1 or HSV2. Most cases of recurrent genital herpes are caused by HSV2, being the leading cause of genital ulcer disease in developing countries, but the proportion of anogenital herpetic infections attributed to HSV1 are increasing, especially in young women and MSM. The prevalence in the general population ranges from 10% to 80% and depends on socio-economic factors. Seropositivity rates are higher in women than in men and increase with age. Reactivation and subclinical shedding is more frequent in genital infections caused by HSV2 than by HSV1, which reaffirm the importance of laboratory confirmation of clinical diagnosis. Aims: Retrospective study of the role of HSV1 and HSV2 infections in genital ulcerations from a population of a Sexually Transmitted Diseases Outpatient Clinic, according to epidemiological, laboratory and clinical data. Methodology: 56 ulcer genital/urethral swabs from patients suspected of HSV infection were sent to the National Institute of Health (NIH), in Lisbon, between April 2015–April 2016. HSV1 and HSV2 were determined by a quantitative commercial real-time PCR kit, which targets a fragment of 162 bp of a region located in the US7 gene for HSV1 and a fragment of 177 bp of a region located in the US2 gene for HSV2. The 56 swabs were also inoculated in Vero cell cultures for determination of cytopathic effect. Results: HSV infection in genital/urethral swabs were detected in 30 (53.6%) of 56 samples. The symptoms of the positive cases were genital ulcerations in vulva or penis and/or perineum and the clinical diagnosis was genital herpes infection. In 7 of the 30 positive cases (23.3%) HSV1 DNA was detected (2 man and 5 women with age ranges between 17 and 27 years old); and in 23 of the 30 positive cases (76.7%) HSV2 DNA was detected (18 man and 5 women, with age ranges between 17 and 62 years old). Five of the 7 HSV1 positive cases were primoinfections (71.4%) and in the 23 HSV2 positive cases, 3 (13.0%) were primoinfections and 8 (34.8%) were the first ulcer episode but not primoinfections. HSV DNA viral load values varied between 21848–87474493 cop/ml in HSV1 cases and between 1177– 31160846336 cop/ml in HSV2 cases. We didn’t find direct correlation between viral load and primary vs recurrent infection although the higher viral load was found in HSV2 first episode cases. Cytophatic effect was observed in all positive PCR cases. All positive cases were treated with valacyclovir and resolved after treatment. Comments: To identify HSV genital infections is important for the specific treatment, for preventing the transmission of HSV to partners, and to prevent the risk of acquiring and transmitting HIV. In our study 53.6% cases were positive for HSV genital infection; because of social, demographic and migratory tendency, the population at risk for STI continues to grow and experience an increased burden of disease. We also observed in this population an increasing proportion of HSV1 genital primoinfection, which is in accordance to the literature. In the present study we confirmed the usefulness of real-time PCR for HSV DNA detection in genital ulcerations. Concerning the correlation of viral load with subtype, the differences should be further evaluated with an increase number of clinical cases.